Upaya Meningkatkan Minat Beli Omset Penjualan Melalui Sertifikasi Halal Di Kecamatan Tirtoyudo - Retno Gumila Sari; Windi Yuniarti; Sinollah Sinollah (Pakis Journal Institute, 2024)
Indonesia's economic growth is significantly assisted by micro, small, and medium enterprises (UMKM). However, many UMKM in the Tirtoyudo sub-district area are not aware of the importance of product certification. To make business owners aware of the importance of product certification, extensive socialization is needed. As a country with a majority Muslim population, halal certification has a significant impact on consumer interest in a product. This is the motivation behind our devotional research, which aims to educate consumers on the importance of halal certification for food or cosmetics. In addition, so that business owners are aware and understand that managing halal certification is simple and only requires KUA to achieve sub-district level management. The product must be able to compete in the market and broaden its reach in order to generate more revenue.